Development of Geometry Transformation Learning Media by Utilizing Mobile Technology - Janner Simarmata; Muhammad Dani Solihin; Harvei Desmon Hutahaean; Muhammad Isnaini (Jurnal Penelitian Pendidikan IPA, 2024)
This study is dedicated to the creation of geometry transformation learning media through the utilization of Mobile-Based App Inventor and a subsequent comprehensive evaluation of its influence on student academic performance. The research adopts a meticulously structured Research and Development (R&D) methodology, encompassing critical stages such as analysis, design, development, implementation, and evaluation. The culmination of this research journey unveils compelling evidence that underscores the transformative potential of the developed learning media. Through quantitative and qualitative assessments, this study unearths a significant enhancement in students' grasp of the intricate concepts inherent to geometry transformation. The outcomes of this research illuminate the pivotal role of technology, particularly the Mobile-Based App Inventor, in shaping contemporary pedagogical landscapes. The learning media serves as a testament to the symbiotic relationship between innovation and education, offering an engaging and effective resource to empower students in their quest for mathematical proficiency and analytical prowess.